Concurrent presentation of cutaneous lesions of deep linear morphoea and discoid lupus erythematosus. (February 2016) - Bernárdez, C; Prieto-Torres, L; Macías, E; Ramírez-Bellver, J L; Haro-Ramos, R; Diaz-Recuero, J L; Requena, L
Patients with autoimmune disorders are predisposed to develop a second immunologic disease, frequently with systemic involvement. We present a patient who developed lesions of discoid lupus erythematosus (DLE) limited to the face, and, concurrently, a linear morphoea involving her right axilla. No criteria for systemic lupus erythematosus or systemic scleroderma were present in the patient. To our knowledge, no patients with concomitant DLE and linear morphoea, without systemic involvement, have been previously reported in the literature.